Effect of Using Windscreen Glass Waste Powder (WGWP) As Cement Replacement on the Mechanical Properties of Mortar. (June 2020) - Anisah, N.N.; Awang, M.; Kartini, K.
Abstract: Sustainability issues have obtained major attentions around the globe. In this regard, there are challenges which the cement and glass industries are facing due to the high greenhouse gases emissions, the intensive use of energy and the reduction of natural resources on earth. However, the chemical compositions and the pozzolanic properties of waste glass are very encouraging for its use in cement and concrete industries and to provide an environment-friendly solution. For sustainability, it is high time to look into the possibility of replacing cement with windscreen waste glass. A study was conducted on the effects of various proportions of windscreen glass waste powder (WGWP) on the compressive strength of mortar. The mortar was prepared by incorporating several compositions of WGWP (0%, 5%, 10%, 15% and 20% by weight of cement), while three cement to sand (C:S) ratios of 1:2.5, 1:3.0 and 1:3.5 were employed. Fixed water to cement (w/c) ratio of 0.5 was used for this study. The samples were water cured and the assessment of the strength performance of mortar cubes was carried out at 7 and 28 days. Results have shown that WGWP has good pozzolanic properties. In term of compressive strength, it was observed that employing C:S ratio of 1:3.0 is better than 1:2.5 and 1:3.5 of C:S ratio.